Molecular Dynamics Simulations of Aqueous Solutions of KCl at Remote Sensing Frequencies - Feng, Lei; Li, Ke; Yang, Xiao-Qing (Asian Journal of Chemistry, 2013)
In this study, molecular dynamics simulations of aqueous solutions of KCl at mass concentrations between 1 and 8 % and at the temperature ranges from 20 to 30 ºC were investigated. Debye relaxation spectrum equation was used to describe the frequency-dependent complex permittivity. The simulated results were compared with experimental results at 5.1 GHz and 13.6 GHz (frequencies that are commonly used by ocean remote sensing satellites) and proved to approximatively agree with the experimental results.